3D Ductile crack propagation with the XFEM. Issue 1 (11th November 2015) - Beese, Steffen; Loehnert, Stefan; Wriggers, Peter
Abstract: Ductile fracture is of high interest for industrial Manufacturing. Here we attempt to model this material degradation with a combined approach of non‐local continuum damage mechanics and discrete fracture mechanics using the eXtended Finite Element Method. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)